2006
DOI: 10.1177/039139880602900112
|View full text |Cite
|
Sign up to set email alerts
|

The Vicenza “Short” Peritoneal Catheter: A Twenty Year Experience

Abstract: Dislocation of peritoneal dialysis catheters is one of the major causes of technique failure. We evaluated 701 Vicenza catheters, implanted since 1985 in 365 males, mean age 53 ± 16 yrs, range 24 - 87, and 336 females, mean age 51 ± 17 yrs, range 21 - 82. The Vicenza catheter is defined “short” since it consists of a classic straight double cuff PD catheter having however an inner segment (the portion located in the peritoneal cavity) much shorter than any other type of catheter. It is implanted in the lower a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
11
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 5 publications
4
11
0
Order By: Relevance
“…Table 3 shows representative studies of double-cuffed straight catheter placement. The rate of catheter malfunction in the modified open surgery group in our study is comparable to rates reported in earlier studies (19,(28)(29)(30)(31)(32)(33).…”
Section: Review Of the Literaturesupporting
confidence: 90%
See 2 more Smart Citations
“…Table 3 shows representative studies of double-cuffed straight catheter placement. The rate of catheter malfunction in the modified open surgery group in our study is comparable to rates reported in earlier studies (19,(28)(29)(30)(31)(32)(33).…”
Section: Review Of the Literaturesupporting
confidence: 90%
“…As a proof of concept, the present study has shown (as have others) a promising decrease in catheter malfunction with modification of the open surgery procedure (19,29,30,33). Although the use of a low incision site has previously been reported, the introduction in this study of an individualized length of catheter, coupled with a long, straight, upward tunnel, may bring more potential benefits to catheter placement, as has already been discussed.…”
Section: Mechanical Complicationssupporting
confidence: 73%
See 1 more Smart Citation
“…Up to now, open surgery is still the most commonly used PD catheter insertion technique. Previous studies showed that a short, mobilizable intra‐abdominal catheter was useful in reducing catheter malfunction . However, the implant position of traditional open surgery is 11 cm above the pubic symphysis with a long length of intra‐abdominal catheter segment, which might lead to a high incidence of catheter tip migration and omentum wrap.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies showed that a short, mobilizable intra-abdominal catheter was useful in reducing catheter malfunction. 12,13 However, the implant position of traditional open surgery is 11 cm above the pubic symphysis with a long length of intra-abdominal catheter segment, which might lead to a high incidence of catheter tip migration and omentum wrap. It is reported that 7.6-17.1% of patients developed catheter tip migration when using this open technique.…”
Section: Discussionmentioning
confidence: 99%